The availability and affordability of selected essential medicines for chronic diseases in six low- and middle-income countries - Shanti Mendis; Keiko Fukino; Alexandra Cameron; Richard Laing; Anthonio Filipe Jr; Oussama Khatib; Jerzy Leowski; Margaret Ewen (The World Health Organization, 2007)
OBJECTIVE: To assess the availability and affordability of medicines used to treat cardiovascular disease, diabetes, chronic respiratory disease and glaucoma and to provide palliative cancer care in six low- and middle-income countries. METHODS: A survey of the availability and price of 32 medicines was conducted in a representative sample of public and private medicine outlets in four geographically defined areas in Bangladesh, Brazil, Malawi, Nepal, Pakistan and Sri Lanka. We analysed the percentage of these medicines available, the median price versus the international reference price (expressed as the median price ratio) and affordability in terms of the number of days' wages it would cost the lowest-paid government worker to purchase one month of treatment. FINDINGS: In all countries < 7.5% of these 32 medicines were available in the public sector, except in Brazil, where 30% were available, and Sri Lanka, where 28% were available. Median price ratios varied substantially, from 0.09 for losartan in Sri Lanka to 30.44 for aspirin in Brazil. In the private sector in Malawi and Sri Lanka, the cost of innovator products (the pharmaceutical product first given marketing authorization) was three times more than generic medicines. One month of combination treatment for coronary heart disease cost 18.4 days' wages in Malawi, 6.1 days' wages in Nepal, 5.4 in Pakistan and 5.1 in Brazil; in Bangladesh the cost was 1.6 days' wages and in Sri Lanka it was 1.5. The cost of one month of combination treatment for asthma ranged from 1.3 days' wages in Bangladesh to 9.2 days' wages in Malawi. The cost of a one-month course of intermediate-acting insulin ranged from 2.8 days' wages in Brazil to 19.6 in Malawi. CONCLUSION: Context-specific policies are required to improve access to essential medicines. Generic products should be promoted by educating professionals and consumers, by implementing appropriate policies and incentives, and by introducing market competition and/or price regulation. Improving governance and management efficiency, and assessing local supply options, may improve availability. Prices could be reduced by improving purchasing efficiency, eliminating taxes and regulating mark-ups.